PERAN SULTAN SULAIMAN AL-QANUNI DALAM MEMBANGUN KEJAYAAN KESULTANAN TURKI UTSMANI PADA ABAD KE-16 - HANI HANIFAH El-Ustadzi (IAIN Syekh Nurjati Cirebon, 2017)
The writing attempts to describe the reign of the Ottoman Empire in the 16th century, especially during the reign of Sultan Sulayman al-Qanuni. During the reign, he was able to bring glory to the Ottoman Ottoman Empire. One of the ways that is done by making policies (legislation) which is very appropriate and able to change the order of the Ottoman Turkish Sultanate system becomes more controlled and neat administratively. This research uses library research approach with historical study method through four stages, namely data collection (heuristic), verification, interpretation, and writing (historiography). Sultan Sulaiman Al-Qanuni is a leader who has a very strong soul, especially in building the glory of the Ottoman Empire Sultanate. So he was given the title